MANAGEMENT TECHNIQUE, GOVERNANCE, AND MANAGEMENTSTRATEGY FOR PERFORMANCE AND BUSINESS ETHICS OF PUBLIC SERVICE HOSPITALS - Devid Putra Arda (Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2020)
Abstract The purpose of this paper is to test management technique, governance, and strategy choices affect the performance of government hospitals assigned as public service agencies.Indonesian’s well aware of opting for medical treatments in hospital are basically underlined by higher level education, prolonged life expectancy, and more information disclosure. This awareness leads to significant increases in number of inpatients and outpatients treated in public health services.This research belongs to quantitative research which implements validity test, reliability test, normality test, multicollinearity test, and heteroskedasticity test. Quantitative research is required to examine whether the instruments used in this study are valid, consistent, and normally distributed. This study consist of one dependend variabel namely performance, three independent variables, namely management technique, GCG, and management strategies. Supplemented by one moderation variable, business ethics. This research employs an explanatory design, comprising an elucidation of events in present conditions (explanation) and events that will occur (prediction). The sampling technique used was purposive sampling with sampling criteria that are at the level of administrative staff up to the directors and have worked for at least one year. Based on predetermined criteria, there were 260 research respondents. Data was collected using a questionnaire and measured on a Likert scale of 1-5 with a value of 1 for answers that strongly disagree and a value of 5 for answers strongly agree. The data analysis technique used is multiple regression analysis with the help of SPSS 22. Based on the above findings and discussions, the limitations for future research are elaborated as follows: the level of understandings possessed by respondents regarding the concept of hospitals as public service agencies varies and cannot be controlled or specified. Stakeholders from different occupational positions may have different experiences and educational backgrounds which may affect their understanding of public service agency, particularly the hospital. For this reason, mapping specific respondents might be required for future research. Categorized and specified respondents could optimize the research process by providing more focused answer from and more thorough discussion with stakeholders with the same understanding level. This research can be developed by extending the coverage of hospitals granted with the BLU authorization throughout Indonesia. Besides, alternative research object can also developed by examining non-BLU hospitals. This research concludes Corporate Governance is positive influencer for and significant to Performance; in contrast, Management Strategy is insignificant to Performance. Besides, Ethics itself indirectly influences performance. This study is useful for regulators as policy makers to improve professionalism and improve hospital services. It is also hoped that the results of this study will benefit other stakeholders, change business-oriented mindset without neglecting services and human values. Keywords: Management Technique, Governance, Management Strategy, Performance, Business Ethics, Public Service Hospitals.